Analysis of classroom silence behaviors among Chinese and Korean undergraduates - Zhang, Jinkai; Fang, Zhuotao; Rhee, Gina Sharotte (Frontiers in Psychology, 2025)
IntroductionThis study investigates classroom silence among Chinese and Korean undergraduates using an integrated cultural–psychological model. Drawing on Hofstede’s cultural dimensions, Cramer’s defense mechanism theory, and Fredricks’ engagement framework, classroom silence is conceptualized as both a culturally adaptive practice and a psychologically mediated form of participation.MethodsSurvey data from 913 Chinese and 189 Korean students were analyzed using confirmatory factor analysis (CFA), structural equation modeling (SEM), and multiple indicators multiple causes (MIMIC) modeling to validate the measurement structure, evaluate the hypothesized relationships, and assess demographic influences.ResultsSpeaking anxiety and contextual rigidity emerged as the strongest positive predictors of classroom silence, whereas self-efficacy had the strongest negative effect and served as a key mediator linking environmental and peer factors to silence. Cross-cultural comparisons showed that Chinese students’ silence was primarily shaped by hierarchical, teacher-centered classroom structures, whereas Korean students’ silence was more influenced by gender norms and peer-group expectations. The interaction between self-efficacy and contextual constraints was significant only among Chinese students, indicating cultural variation in coping responses.DiscussionThese findings extend cultural and engagement theories by demonstrating that classroom silence functions as a regulated participation strategy rather than mere disengagement. Pedagogically, the results highlight the importance of fostering students’ expressive self-efficacy, reducing excessive teacher authority, and promoting supportive peer environments. Limitations include the cross-sectional design and unequal group sizes. Longitudinal or mixed-methods research is recommended to examine the developmental pathways of classroom silence across cultural contexts.